Marketing strategy in a homestay industry : a case study of Nihao Taipei guesthouse in Taiwan - Pow, Lay Hooi (2014)
This research is to study about the marketing strategy and strategy formulation adopted by Nihao Taiei Guesthouse, a guesthouse with Taiwnese art and culture. Better income has encouraged a lot of people go for a vacation to recharge and relax from the busy working liife. The recent trend showed that hotel is no longer the only choice for the tourists, the acceptance level of homestayare keep on increasing especially in teenagers and budget travellers as well as those who like to make friends and interact with other tourists from other countries.Taiwan is famous with their homestayand also the friendly culture. People now not only pay for the services and environment of a homestay but also the values and concepts carry by the homestay.